A case of Legionella pneumonia after robot‐assisted radical prostatectomy - Takuhisa Nukaya; Kiyohito Ishikawa; Kiyoshi Takahara; Masashi Takenaka; Kenji Zennami; Manabu Ichino; Hitomi Sasaki; Makoto Sumitomo; Ryoichi Shiroki (IJU Case Reports, 2024)
Introduction Postoperative Legionella pneumonia is very rare. Case presentation A 71‐year‐old male patient with prostate cancer (cT2bN0M0) underwent a robotic‐assisted radical prostatectomy. On the 5th postoperative day, the patient developed chills and a fever of 39.2°C. Chest radiography revealed decreased permeability in the right middle lung field, leading to the diagnosis of postoperative pneumonia. Antimicrobial therapy was initiated immediately. Blood tests on postoperative day 10 revealed mild liver function abnormalities, electrolyte abnormalities, and a markedly elevated inflammatory response. Legionella pneumonia was suspected based on blood sample results and systemic symptoms, such as diarrhea and nausea. Furthermore, Legionella antigens were detected in the patient's urine, prompting further administration of levofloxacin. The patient's subsequent clinical course was favorable. Conclusion When bacterial pneumonia fails to respond to antimicrobial therapy and systemic symptoms develop, atypical pneumonia, caused by pathogens such as Legionella pneumophila, should be considered even in cases of postoperative pneumonia.